Visual Basic® .NET Power Coding - Kimmel, Paul (Addison-Wesley Professional, 2003)
Visual Basic® .NET Power Coding is the experienced developer's guide to mastering advanced Visual Basic .NET concepts. Paul Kimmel saves readers time and money by providing thorough explanations of essential topics so you can quickly begin creating robust programs that have fewer bugs. He also demonstrates important concepts by using numerous real-world examples that include working code that has been tested against Visual Basic .NET 2003. After a brief review of language idioms, Kimmel moves to more advanced techniques that help programmers solve their most challenging problems. Central to advanced development and deployment are chapters on security, Web services, ASP.NET programming, COM Interop, and Remoting. This book also covers thin client programming, which offers businesses a real solution to managing deployment and upgrades with Windows Forms using Reflection and HTTP. An appendix walks readers through migrating Visual Basic 6.0 applications to Visual Basic .NET. A companion Web site includes the complete downloadable source code, extensive reusable examples, and updates from the author. This book can be read cover-to-cover or used as a reference to answer questions faced by experienced VB .NET developers, including: Chapter 4: What can you do with Reflection technology? Chapter 6: How can you safely incorporate multithreaded behavior into Visual Basic .NET applications? Chapter 8: How would you serialize objects and implement Remoting for distributed projects? Chapter 14: How do you return an ADO.NET DataSet from a Web service? Chapter 18: What are the best practices for securing Web applications? Visual Basic® .NET Power Coding empowers developers to exploit all the advanced features of Visual Basic .NET. 0672324075B06062003.